2018
DOI: 10.1109/tvcg.2017.2743898
|View full text |Cite
|
Sign up to set email alerts
|

Imagining Replications: Graphical Prediction & Discrete Visualizations Improve Recall & Estimation of Effect Uncertainty

Abstract: People often have erroneous intuitions about the results of uncertain processes, such as scientific experiments. Many uncertainty visualizations assume considerable statistical knowledge, but have been shown to prompt erroneous conclusions even when users possess this knowledge. Active learning approaches been shown to improve statistical reasoning, but are rarely applied in visualizing uncertainty in scientific reports. We present a controlled study to evaluate the impact of an interactive, graphical uncertai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
46
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
2

Relationship

3
6

Authors

Journals

citations
Cited by 53 publications
(49 citation statements)
references
References 50 publications
3
46
0
Order By: Relevance
“…For dot encodings, perceived causality did not differ significantly between aggregation level two (M=87. 19 33, 68.20]).…”
Section: Causation Judgment Resultsmentioning
confidence: 99%
“…For dot encodings, perceived causality did not differ significantly between aggregation level two (M=87. 19 33, 68.20]).…”
Section: Causation Judgment Resultsmentioning
confidence: 99%
“…Prior work in visualization and judgment and decision making suggests that different subjective probability elicitation techniques can produce varying results, perhaps because some techniques (such as frequency framings) better align with people's internal representations of uncertainty [15,22,40]. In a second study, we assess how sensitive people's responses are to different elicitation methods, which vary in the input format for beliefs they use (i.e., continuous probability versus discrete samples).…”
Section: Developing Research Questions and Goalsmentioning
confidence: 99%
“…Sample-based Elicitation. Evidence from research on reasoning with uncertainty (e.g., on classical Bayesian reasoning tasks [12]) and uncertainty visualization [9,22,23,26,27] indicates that people are often better at thinking about uncertainty when it is framed as frequency rather than probability. One way to elicit uncertainty is through a technique that asks people to provide one sample at a time until they have exhausted their mental representation.…”
Section: Developing Elicitation Techniques and Conditionsmentioning
confidence: 99%
“…They suggested that people using the interactive models exhibited higher accuracy in Bayesian reasoning compared to previous methods. Hullman et al (2018) suggested a novel interactive, graphical uncertainty prediction technique for communicating uncertainty in experimental results by letting users to graphically predict the possible effects from experiment replications prior to seeing the true sampling distribution. The study showed that users were able to make better predictions about replications of new experiments through this technique.…”
Section: Interactive Techniquesmentioning
confidence: 99%